Brain Drain Among Nepalese Health Professionals: Causes, Consequences, and Potential Solutions - Giri, Suja; Limbu, Binod; Dahal, Dipak Prasad; Singh, Neha; Pahari, Sirjana Pandit; Poudel, Mukunda; Khanal, Ashish (Journal of Multidisciplinary Research Advancements, 2025)
This study comprehensively analyses the brain drain phenomenon among Nepalese health professionals, addressing its historical context, underlying causes, and potential solutions. The paper identifies the gaps in existing literature by examining the global migration of highly educated individuals from developing to developed countries. It seeks to offer a detailed understanding of this complex issue. The primary objective of this study was to explore the impact of brain drain on the healthcare industry, considering its implications for both source and destination countries. Through an in-depth literature review, the paper presents key findings related to the various forms of brain drain, including organisational, industrial, and geographic, and their consequences for healthcare delivery. Furthermore, the paper focuses on recent studies that challenge the traditional perspective on the causes of the shortage of educated workers in developing nations, offering a more contentious viewpoint. The paper emphasises the need for targeted interventions and policy measures to address the challenges posed by brain drain while also recognising the fundamental right of migrant healthcare workers to seek improved opportunities for themselves and their families.